2012
DOI: 10.3399/bjgp12x656810
|View full text |Cite
|
Sign up to set email alerts
|

When and how do GPs record vital signs in children with acute infections? A cross-sectional study

Abstract: Background NICE recommendations and evidence from ambulatory settings promotes the use of vital signs in identifying serious infections in children. This appears to differ from usual clinical practice where GPs report measuring vital signs infrequently. AimTo identify frequency of vital sign documentation by GPs, in the assessment of children with acute infections in primary care. Design and settingObservational study in 15 general practice surgeries in Oxfordshire and Somerset, UK. MethodA standardised profor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…In this national non-hospital-based cross-sectional prospective study, we report wide differences between current recommendations and observed practices of a large number of HPs (GPs, pediatricians and pharmacists) for the symptomatic management of fever in nearly 6,600 children. Contrary to recommendations [ 3 ] and as noted previously [ 30 , 31 ], temperature, a major vital sign, was recorded for only 40% of children during consultations with physicians. A least one drug was almost systematically (> 90%) prescribed by GPs and pediatricians and frequently advised by pharmacists for patients without a previous consultation (> 70%).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In this national non-hospital-based cross-sectional prospective study, we report wide differences between current recommendations and observed practices of a large number of HPs (GPs, pediatricians and pharmacists) for the symptomatic management of fever in nearly 6,600 children. Contrary to recommendations [ 3 ] and as noted previously [ 30 , 31 ], temperature, a major vital sign, was recorded for only 40% of children during consultations with physicians. A least one drug was almost systematically (> 90%) prescribed by GPs and pediatricians and frequently advised by pharmacists for patients without a previous consultation (> 70%).…”
Section: Discussioncontrasting
confidence: 86%
“…We were able to study various determinants of HPs’ practices related to parents, the child or the HPs themselves. As in other studies, the temperature was not systematically measured by physicians (40% vs. 25% to 54%) [ 30 , 31 ] and less often when parents had taken the temperature before the consultation and when this measurement was adequate (i.e., when parents measured the temperature with an electronic thermometer by a rectal, oral, auricular or axillary route). This situation may reflect a certain degree of confidence in the information provided by parents and a lack of time during busy consultations.…”
Section: Discussionmentioning
confidence: 98%
“…[ 33 ] Moreover, the inconsistent and non-standardized measurement of CRT in clinical practice may also reduce the potential utility of this vital sign. [ 34 , 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with a previous study that showed that overall documentation of vital signs by GPs is relatively poor in children presenting with acute infections. 12 …”
Section: Discussionmentioning
confidence: 99%